The role of TREM2 in Alzheimer’s disease: from the perspective of Tau - Huang, Wendi; Huang, Juan; Huang, Nanqu; Luo, Yong (Frontiers in Cell and Developmental Biology, 2023)
Triggering receptor expressed on myeloid cells 2 (TREM2), a pattern recognition receptor abundantly expressed on microglia, has been identified as one of the risk factors for Alzheimer's disease (AD). Several studies have already demonstrated the relationship between TREM2 and Tau.TREM2 mutations and altered expression play an important role in Tau phosphorylation. Furthermore, the level of Tau phosphorylation is correlated with soluble TREM2 (sTREM2). However, in different stages of AD, TREM2 seems to have varying effects on Tau pathology. The explicit interaction between TREM2 and Tau, as well as how they affect AD pathology, remains unclear, and there is much evidence to the contrary that requires rational interpretation. Reviewing the dual roles of TREM2 in AD will help identify a more appropriate development strategy for targeting TREM2 to treat AD.Therefore, this review focuses on the interplay between Tau and TREM2 in relation to AD.